Qur’anic Inquisitive Thinking (QIT): a study of the questions and questioning styles in the Qur’an - Badi, Jamal Ahmed Bashier; Machouche, Salah (2015)
Muslim scholars across their various religious disciplines whether traditional or rational disciplines have drawn extensively on the revelation and as a result produced interesting fields of inquiry. Despite their extensive work however, the question of cognitive development however has not yet received adequate attention in contemporary Islamic scholarship. Researchers often draw on scattered information in both early and later Quranic exegeses in addition to some other works on spiritual and moral disciplining of the human self (adab al-nafs). The current research is based on the belief that the Quran raises logical, powerful and comprehensible questions in the way it conveys the message of the Creator. Nonetheless, those questions exercise significant influence on the development of inquisitive thinking. This study seeks to exploring the issue of inquisitive thinking by way of investigating the possible connections between selected questions in the Qur’an and the overall development of human thinking. The research explores the various relationships coordinating the Quranic questions and the cognitive development especially during times of recitation and reflection. The research also examines the taxonomy of human inquisitive thinking with relation to the various types of Qur’anic questions and question making styles. Using an interdisciplinary approach of inquiry, this study uses the analytical method based on surveying the Qur’anic questions covering selected themes.